Water in the environment tainted life source hungers for cures - Lau, Seng (Universiti Malaysia Sarawak (UNIMAS), 2011)
In the past two decades, the author has conducted research mainly on the inland water quality in Sarawak. Most of the river in Sarawak were classified as Class III river (slightly polluted). Those river that drain urban areas were rated as Class IV and Class V (very polluted). Those river from the head water areas were found to be still in their pristine state of Class II. The main pollutants for most of the rivers were the suspended solids as a result of soil erosions, untreated sewage and animal wastes from livestock farms.